Benefits of Intergenerational Programs for children and adolescents with mental disorders risk factors: An integrative review (Research, Society and Development, 2024)
Intergenerational programs provide interaction opportunities between younger and older generations in activities that promote both physical and mental well-being for those involved.  Proposals investing in these projects in favor of preventive actions for childhood and adolescence mental health have already revealed the potential contribution of these practices for mental care prevention in this period of life. In this sense, the objective of the current study is to identify possible benefits of intergenerational programs for children and adolescents vulnerable to the development of mental disorders, using for this purpose an integrative review of the literature, as it allows the inclusion of experimental and non-experimental studies, combining theoretical data and empirical literature, for an expanded and current understanding of the topic under analysis. By means of searching LILACS, Cochrane, PsycINFO, PubMed and Web of Science databases and using the life cycle approach to risk factors for mental disorders, 283 articles were identified, from which only three were included. The selected studies described intergenerational programs which had positive outcomes for children and adolescents involved, such as increased self-esteem, improved interpersonal relationships, lower stress and greater life satisfaction. Using scientific correlations from well-established research, such outcomes could be interpreted as benefits for the mental health of children and adolescents with mental disorders risk factors. Thus, the review proposes a new point of view to deepen studies in future research on the role that intergenerational programs can play in mental health prevention of pediatric population.